Improve Flour Quality by use Oxidized Agent during Tempering of Local Wheat - Sakena Taha Hasan (Journal of Global Pharma Technology, 2018)
The Objective of this study was examined the effect of Oxidized Agent (hydrogen peroxide) added to temper water in order modify the quality of the local wheat flour. Chemical properties (protein, ash) and wet, dry gluten, gluten index and color. Rheological properties were measured by the farinograph, amylograph. Bread quality (Specific volume, Sensory evaluation). The hydrogen peroxide was added at three different levels (0, 0.01, 0.03%) to temper water wheat. Addition of hydrogen peroxide during tempering water wheat led to no significant increase in protein, ash, color and wet, dry gluten contained, but led to significant increase in gluten index. Addition hydrogen peroxide led to no significant increase on farinograph parameters. No significant effect on begin of gelatinization and viscosity temperature but there is significant positive effect on peak of viscosity curve. Significant positive effect on dough and bread quality, improved dough process Specific volume, crust color, symmetry of form, taste and chew ability. The optimal dose of hydrogen peroxide is (0.03%).Keywords: Hydrogen peroxide, Tempering, Local wheat, Dough rheology, Gluten, bread.